Balthasar Neumann als fürstbischöflicher Baukommissar - Süßmann, Johannes (Die Kunst der Mächtigen und die Macht der Kunst. Untersuchungen zu Mäzenatentum und Kulturpatronage)

Vergemeinschaftung durch Bauen. Würzburgs Aufbruch unter den Fürstbischöfen aus dem Hause Schönborn - Süßmann, Johannes

Middleware for Secure Home Access and Control - Marin, Andres; Müller, Wolfgang; Schäfer, Robbie; Almenarez, Florina; Diaz, Daniel; Ziegler, Max (Proc. of the IEEE PerCom Middleware Support for Pervasive Computing (PerWare 2007))
User adaptive systems in the context of pervasive computing can only unveil their power if based on a generic middleware managing private data and context information in combination with flexible device access and control. However, managing those data poses severe privacy problems both legally and from a trust perspective. Therefore we propose a home automation middleware for secure management of user and context data that gives access to services just for the authorized users and devices. The middleware has been successfully tested at the ambient computing (AC-LAB) at the University of Paderborn.

Coherent Semiconductor Optics - Meier, Torsten; Thomas, Peter; Koch, Stephan W.

Gottesdienst-Orte. Handbuch Liturgische Topologie. Günter Ruddat zum 60. Geburtstag

The Virtual Resource Manager: Local Autonomy versus QoS Guarantees for Grid Applications - Burchard, Lars-Olof; Heine, Felix; Heiss, Hans-Ulrich; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry; Schneider, Jörg (Future Generation Grids)
In this paper, we describe the architecture of the virtual resource manager VRM, a management system designed to reside on top of local resource management systems for cluster computers and other kinds of resources. The most important feature of the VRM is its capability to handle quality-of-service (QoS) guarantees and service-level agreements (SLAs). The particular emphasis of the paper is on the various opportunities to deal with local autonomy for resource management systems not supporting SLAs. As local administrators may not want to hand over complete control to the Grid management, it is necessary to define strategies that deal with this issue. Local autonomy should be retained as much as possible while providing reliability and QoS guarantees for Grid applications, e.g., specified as SLAs.

Introducing Risk Management into the Grid - Djemame, Karim; Gourlay, Iain; Padgett, James; Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on e-Science and Grid Computing)

The First Step of Introducing Risk Management for Prepossessing SLAs - Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Services Computing (SCC))

Risk Aware Migrations for Prepossessing SLAs - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Mechanical and Hybrid Joining - Meschut, Gerson (Magnesium Technology)

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

The strategic advantage of interdependent preferences in rent-seeking contests - Guse, T.; Hehenkamp, Burkhard (Public Choice)

Maintaining Communication Between an Explorer and a Base Station - Dynia, Miroslaw; Kutyłowski, Jarosław; Lorek, Paweł; Meyer auf der Heide, Friedhelm (IFIP International Federation for Information Processing)

Set Oriented Numerical Methods in Space Mission Design - Dellnitz, Michael; Junge, Oliver (Elsevier Astrodynamics Series)

Investigation of colour phenomena in condensed water droplets - Wetzlar, Dietmar; Henning, Bernd; Nolte, Sascha; Klahold, Jens
Today's automotive headlights are built with transparent cover lenses. Therefore condensation of water leads to a visible optical defect. This paper presents a new approach for determination of the droplet size using colour phenomena in totally reflected light. It is based on a model of the generation of colour patterns by interference of several rays of light each multiple totally reflected inside condensed droplets. The droplet size may be determined by the colour if the contact angle is known. Measurement of both droplet size and colour all

Organic molecule adsorption on solid surfaces: chemical bonding, mutual polarisation and dispersion interaction - Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Hermann, A.; Ortmann, F.; Bechstedt, F. (Applied Physics A)

Quasiparticle corrections to the electronic properties of anion vacancies at GaAs(110) and InP(110) - Hedström, Magnus; Schindlmayr, Arno; Schwarz, Günther; Scheffler, Matthias (Physical Review Letters)
We propose a new method for calculating optical defect levels and thermodynamic charge-transition levels of point defects in semiconductors, which includes quasiparticle corrections to the Kohn-Sham eigenvalues of density-functional theory. Its applicability is demonstrated for anion vacancies at the (110) surfaces of III–V semiconductors. We find the (+/0) charge-transition level to be 0.49 eV above the surface valence-band maximum for GaAs(110) and 0.82 eV for InP(110). The results show a clear improvement over the local-density approximation and agree closely with an experimental analysis.

Denken in Darstellungen – Schiller und die Geschichte - Süßmann, Johannes (Schiller und die Geschichte)

On the Distribution of the Desirability Index using Harrington’s Desirability Function - Trautmann, Heike; Weihs, C (Metrika)
The concept of desirability is a means for complexity reduction of multivariate quality optimization. This paper provides a theoretical breakthrough regarding desirability indices, which application fields were formerly limited primarily by the lack of its distribution. Focussed are the distributions of Harrington’s desirability functions and different types of the desirability index.

A Formal Behavioral Semantics for TestML - Großmann, Jürgen; Müller, Wolfgang (Proc. of ISOLA 06)
TestML is an XML-based language for the exchange of test descriptions in automotive systems design and mainly introduced through the structural definition of an XML schema as an independent exchange format for existing tools and methods covering a wide range of different test technologies. In this paper, we present a rigorous formal behavioral semantics for TestML by means of Abstract State Machines (ASMs). Our semantics is a concise, unambiguous, high-level specification for TestML-based implementations and serves as a basis to define exact and well-defined mappings between existing test languages and TestML.
Keywords: System testing; Software testing; Automotive engineering; Automatic testing; Machinery production industries; Protocols; Hardware design languages; Samarium; XML; Computer industry